Enhancing Teachers’ Organizational Citizenship Behavior: Evidence from Islamic Junior Schools on the Impact of Support, Leader-Member Exchange, and Job Characteristics - Ahmad Almafahir; Mustaqim Mustaqim; Fahrurrozi Fahrurrozi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Organizational Citizenship Behavior (OCB) among teachers plays a pivotal role in enhancing school effectiveness. However, research on its antecedents in faith-based educational settings, particularly Islamic junior schools, remains limited. This study investigates how perceived organizational support (POS), leader–member exchange (LMX), and job characteristics influence teachers’ OCB. A quantitative correlational design was used involving 173 teachers from 20 Islamic junior schools in Pandeglang, Indonesia, selected via cluster random sampling. Validated Likert-scale instruments measured the four constructs. Data were analyzed using SPSS 29 through linear regressions and ANOVA, with classical assumption tests ensuring model validity. All three predictors—POS, LMX, and job characteristics—showed significant positive effects on OCB. Job characteristics emerged as the strongest predictor, explaining 87.8% of the variance. Collectively, the three factors accounted for 90.5% of OCB variance. Among demographic variables, only length of service significantly influenced OCB, with more experienced teachers reporting higher levels. Findings underscore the importance of enriching job design, fostering supportive leadership, and enhancing organizational support to cultivate voluntary, extra-role behaviors in teachers. The high explained variance suggests strong alignment between these organizational factors and OCB, particularly in culturally and spiritually embedded school environments. The study contributes to extending Social Exchange Theory and the Job Characteristics Model within the context of Islamic education. Future research should consider multi-source data and longitudinal designs to further validate these findings.